PELAKSANAAN PEMBELAJARAN SENI BUDAYA (SENI MUSIK) MENGGUNAKAN METODE DEMONSTRASI DI KELAS XI F1 SMA NEGERI 1 2 X 11 ENAM LINGKUNG (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the implementation of music education using the demonstration method for the topic of musical transposition in class XI F1 at SMA Negeri 1 2×11 Enam Lingkung. Studying employs a qualitative approach with a descriptive method. The research subjects were the Arts and Culture (Music) teacher and the students of class XI F1 at SMA Negeri 1 2×11 Enam Lingkung. The object of the study was the implementation of music instruction using the demonstration method for the topic of musical transposition. Data was collected through observation, interviews, and documentation, and subsequently analyzed using techniques comprising data reduction, data presentation, and conclusion drawing. The results indicate that the demonstration method in music instruction was implemented through preparation, execution, and evaluation stages. Supporting factors for the implementation included teacher competence, the availability of instructional media, student enthusiasm, and a conducive learning environment. Meanwhile, inhibiting factors included limited instructional time, variations in students' musical abilities, incomplete musical instruments brought by students, and a lack of focus among some students during the learning process.